Frequency of Successful Vaginal Delivery after Induction of Labour in Obese Pregnant Women Presenting at Tertiary Care Hospital Peshawar - Aqsa Latif, Maimoona Azam, Hina Khan, Madiha Iqbal, Imran Khan, Zakia Khan, Shagufta Naz, Muhammad Sabtain Abid, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: The incidence of induction of labour is 20% of all deliveries and is considered as the most common techniques in modern obstetrics. But both medically indicated and elective inductions are thought to increase the risk of instrumental and cesarean deliveries. Objective: Aim of this study was to determine the frequency of successful vaginal delivery after induction of labour in obese women. Methodology: This study was descriptive study carried out at Gynecology and Obstetrics Department, Hayatabad Medical Complex, Peshawar. The duration of study was Six months (from 1/2/2021 to 1/8/2021). Detail history, clinical examination, routine investigation were performed for the confirmation of obese pregnant women. All the data i.e. age, gestational age, parity, gravidity, number of induction, duration of labour, previous history of C section was recorded in pre design performa. All the recorded information on performa was entered in statistical software SPSS ver 23. Results: Our study shows that among 149 patients mean maternal age was 29 years with standard deviation ± 5.91. Among 149 patients successful vaginal delivery was observed in 86(58%) patients while 63(42%) patients were observed with un-successful vaginal delivery. Conclusion: Our study concludes that the frequency of successful vaginal delivery was 58% after induction of labour in obese pregnant women presenting at tertiary care hospital Peshawar. Keywords: Successful vaginal delivery, Induction of labour, obese pregnant women